Liver resection versus transcatheter arterial chemoembolization for the treatment of patients with hepatocellular carcinoma and hepatic vein or inferior vena cava tumor thrombus: A propensity score matching analysis. Issue 4 (28th January 2019) - Chen, Zhen‐Hua; Zhang, Xiu‐Ping; Wang, Kang; Sun, Ju‐Xian; Chai, Zong‐Tao; Yang, Yang; Guo, Wei‐Xing; Shi, Jie; Lau, Wan Yee; Cheng, Shu‐Qun
Abstract : Aim: Because of the rarity of hepatic vein tumor thrombus (HVTT) in patients with hepatocellular carcinoma (HCC), little is known about HVTT. Thus, the survival benefit of liver resection (LR) versus transcatheter arterial chemoembolization (TACE) for HCC patients with HVTT or inferior vena cava tumor thrombus (IVCTT) remains controversial. We aimed to explore the survival benefits of LR versus TACE for the treatment of these patients. Methods: From 2012 to 2016, a total of 276 patients with HVTT or IVCTT who underwent liver resection or TACE were enrolled in this study. Patients in the LR group were matched at a 1:1 ratio with patients treated with TACE as an initial treatment (TACE group). Clinical characteristics, overall survival, and disease‐free survival were analyzed. Results: The median survival time in the LR group was 4.7 months longer than that in the TACE group before PSM (19.4 vs. 14.7 months, P  = 0.006) and 6.9 months longer than that in the TACE group after PSM (20.9 vs. 14.0 months, P  = 0.019). The median disease‐free survival time in the LR group was 3.2 months longer than that in the TACE group before PSM (12.3 vs. 9.1 months, P  = 0.038) and 5.8 months longer than that in the TACE group after PSM (13.0 vs. 7.2 months, P  = 0.011). Conclusion: Liver resection provides a good prognosis for HCC patients with HVTT or IVCTT compared with patients undergoing TACE, and coexistence with portal vein tumor thrombus is the most important factor related to survival.